RISK MANAGEMENT ANALYSIS IN SMALL AND MEDIUM ENTERPRISE OF WOODEN TRADITIONAL HOUSE INDUSTRY IN WOLOAN - Wuntu, Gratia; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Small and medium businesses are one of the informal sectors.In wooden traditional house industry, the sale is one risk will influence the profit gained to predict the risk that may occur it needs analysis of risk. The factor that cause these among others are human natural a technical factors.Why risk should be managed? The answer, that is because the risk of containing costs is not small. Direct losses from these events are the financial loss caused by the burning of assets (eg building, equipment, materials). The wooden traditional houseÂ  industry in Woloan obtains three principal factors that could impede the course of this business. This research uses descriptive analysis and risk analysis, calculated using poissonmethods,as a sample of the research 15 respondents.The result in wooden traditional house industry in Woloan found that those most at risk are difficult acquisition of raw materials (wood). The craftsman and the owner of wooden traditional house in Woloan, should manage the risk especially for difficult acquisition of wood, so in the sequel, the craftsman can produce a product on time for industry survival. Keywords: risk management, risk analysis, risk map, preventive strategy